The Effect of High Dose Vitamin C (ascorbic acid) on Proinflammatory Cytokines in COVID-19 - MD Ayu Mira Cyntia Dewi - (UNUSA Press, 2021)
Background: COVID-19 is a new pandemic that has claimed many lives in many countries. This pandemic was caused by the SARSCoV2. Until now, there is no specific antiviral drug or vaccine against Covid-19 for potential therapy in humans. This virus can cause cytokine storms which can worsen symptoms in sufferers due to an imbalance between increased oxidant production and available antioxidants. Vitamin C is an important antioxidant that protects the body from various bad effects of free radicals. At high concentrations vitamin C plays an important role in immunomodulation. This study was conducted to determine the effect of high doses of vitamin C on levels of pro-inflammatory cytokines in Covid-19. Method: This research type is literature study. The population in this study were journals about Covid-19, vitamin C, antioxidants and free radicals, inflammatory reactions due to viral infections with samples taken from indexed journals published from 2015 to 2020. There are also clinical trials of high doses of vitamin C against inflammation in Covid-19 from these journals. Results: The results of the study in a clinical trial conducted on 54 patients enrolled in 3 hospitals given a 1: 1 ratio for high-dose intravenous vitamin C (HDIVC) or placebo administration. The HDIVC group received 12 g of vitamin C / 50 ml every 12 hours for 7 days at a rate of 12 ml / hour, and the placebo group received bacteriostatic water for injection in the same way. HDIVC administration showed a reduction in inflammatory markers compared to placebo. Conclusion: The conclusion of this study shows that high doses of vitamin C play a role in reducing levels of proinflammatory cytokines.